The Concept of Tasamuh Culture in the Implementation of Multicultural Society Behavior - Ahmad Halid (Universitas Islam Malang, 2023)
This article examines the importance of the concept of tasamuh culture in a multicultural society, this research has succeeded in writing the criteria for tasamuh behavior in pluralism. as a guideline for Muslims in behaving in tasamuh in the midst of a multicultural society. Also as a basis for Jember LPAI residents in carrying out good and forbidding evil in society and government. This article uses descriptive qualitative, active participant observation in Jember LPAI activities once a month every Legi Friday, Tasamuh culture in a multicultural society is orented by the exemplary behavior of the Prophet in the midst of a pluralistic community. He gave an example of a pattern of living together in the midst of theological diversity, culture, racism, language built on the basis of the phrase monotheism (la ilaha illa Allah) in Mecca for 13 years, then he moved to Yathrib (now Medina). Living with a society that does not only consist of one ethnicity, tribe, nation, or religion, but is very diverse. So as to be able to build togetherness in a multicultural society